Comparison of the Fuel Consumption Performance of Rear and Front Wheel Drive Vehicles via Road Test - Ismail, Ahmad Yusuf; Akbar, Abie Anggoardo Sandewa; Firdausy, N (Journal of Applied Sciences, Management and Engineering Technology, 2023)
This paper presents an on-site investigation of a fuel consumption comparison between a Front Wheel Drive (FWD) and Rear Wheel Drive (RWD) vehicle as those are the two most common drive type used in the commercial vehicle. The study focuses on the fuel consumption rate by comparing the average distance achieved by one liter of fuel using the same type of engine. The road test was varied from the normal highway, uphill, downhill, as well as normal city road to give more insight about the fuel consumption characteristics of each variation. From the results, it is known that each road type gives significant different characteristics to the fuel consumption. Also, the comparison between FWD and RWD regarding fuel consumption gives interesting results for further vehicle transmission developments.